Efficacy and safety of fexapotide triflutate in outpatient medical treatment of male lower urinary tract symptoms associated with benign prostatic hyperplasia. (January 2019) - Shore, Neal; Tutrone, Ronald; Roehrborn, Claus G.
Male lower urinary tract symptoms (LUTS) is an increasingly important problem for the majority of late middle aged and elderly men. Fexapotide triflutate (FT) is a first in-class compound given by local injection via the transrectal intraprostatic route under ultrasound guidance. Data from >1700 FT and control injections in prospective randomized blinded controlled multicenter trials are reviewed and discussed in relation to current developments in the field of treatments for LUTS associated with benign prostatic hyperplasia (BPH). Long-term studies of FT in the United States have shown statistically significant improvement in BPH symptoms and objective outcomes including significant reduction in both spontaneous acute urinary retention as well as the subsequent incidence of BPH surgery. FT has been shown to be well tolerated with an excellent safety profile, and is an efficacious clinic-based treatment for BPH involving an intraprostatic injection that requires only a few minutes to administer, with no catheter nor anesthesia requirements.